The effects of worker stress on the job performance in electronic manufacturing - Nurul Aini, Ibrahim (2013)
Electronic manufacturing are under a great deal of worker stress and due to many antecedents of stress such as workload, organization change, physical environment and individual factor. One of the affected outcomes of stress is on job performance. The purpose of this study is to identify the relationship and effects of worker stress on the job performance of electronic manufacturing in Kuantan, Pahang. The data related to the worker stress and job performance were collected from 52 employees in production department of BI Technology Corporation Sdn Bhd. Data was anayzed using Statistical Package of Social Science (SPSS) software version 20.0. Statistical test regression, correlation, reliabilities and t-test used to analysis the data. The results are significant with positive correlation between worker stress and job performance and shows that worker stress has effects on the job performance. So, all alternative hypothesises that state are accepted. The results suggest that organization should facilitate supportive culture within the working atmosphere of the organization.